RELATIONSHIP OF SOCIAL MEDIA USE WITH SOCIAL INTERACTION ABILITY IN ADOLESCENT AT YAPIM NAMORAMBE PRIVATE HIGHT SCHOOL - Tane, Reisy; Sembiring, Friska br. (Jurnal Keperawatan Widya Gantari Indonesia, 2022)
In the era of globalization, social media is very often used for daily needs. The use of social media is carried out by teenagers because of their high curiosity about the most up-to-date information quickly. The objective of this study was to determine whether there is a relationship between the use of social media and the ability of social interaction in adolescents at YAPIM Namorambe Private High School. This study uses a quantitative method with a cross-sectional approach. The number of samples used was 73 students with the total sampling method. This research was conducted at YAPIM Namorambe Private High School from April to May 2022. The data analysis used was the chi-square test. The results of the study explain that 67.1% of the total sample are high social media users. Meanwhile, 36.9% of the total sample uses social media normally. In addition, the social interaction of students at SMA Swasta YAPIM Namorambe is classified as good (64.4%), while the category of social interaction is not good at 35.6%. The data were analyzed using the chi-square test with a p-value of 0.001 which indicates that there is a relationship between the use of social media and social interaction skills. For further research, it is expected to examine other factors that influence social interaction and use more complete methods such as interviews and observations.